Epidemiology, Pathogenesis, and Clinical Approach in Group 5 Pulmonary Hypertension - Al-Qadi, Mazen; LeVarge, Barbara; Ford, H. James (Frontiers in Medicine, 2021)
Pulmonary hypertension (PH) is recognized to be associated with a number of comorbid conditions. Based on these associations, PH is classified into 5 groups, considering common pathophysiologic drivers of disease, histopathologic features, clinical manifestations and course, and response to PH therapy. However, in some of these associated conditions, these characteristics are less well understood. These include, among others, conditions commonly encountered in clinical practice such as sarcoidosis, sickle cell disease, myeloproliferative disorders, and chronic kidney disease/end stage renal disease. PH in these contexts presents a significant challenge to clinicians with respect to disease management. The most recent updated clinical classification schemata from the 6th World Symposium on PH classifies such entities in Group 5, highlighting the often unclear and/or multifactorial nature of PH. An in-depth review of the state of the science of Group 5 PH with respect to epidemiology, pathogenesis and management is provided. Where applicable, future directions with respect to research needed to enhance understanding of the clinical course of these entities is also discussed.